The MYB transcription factor TaPHR3-A1 is involved in phosphate signaling and governs yield-related traits in bread wheat. (29th July 2020) - Zheng, Xingwei; Liu, Cheng; Qiao, Ling; Zhao, Jiajia; Han, Ran; Wang, Xiaolu; Ge, Chuan; Zhang, Wenyun; Zhang, Shuwei; Qiao, Linyi; Zheng, Jun; Hao, Chenyang
Abstract: Improved inorganic phosphate (Pi) use efficiency in crops will be important for sustainable agriculture. Exploring molecular mechanisms that regulate Pi uptake could provide useful information for breeding wheat with improved Pi use efficiency. Here, a TaPHR3-A1 (Gene ID: TraesCS7A02G415800) ortholog of rice OsPHR3 that functions in transcriptional regulation of Pi signaling was cloned from wheat chromosome 7A. Ectopic expression of TaPHR3-A1 in Arabidopsis and rice produced enhanced vegetative growth and more seeds. Overexpression in transgenic rice led to increased biomass, grain number, and primary panicle branching by 61.23, 42.12, and 36.34% compared with the wild type. Transgenic wheat lines with down-regulation of TaPHR3-A1 exhibited retarded growth and root hair development at the seedling stage, and showed yield-related effects at the adult stage when grown in both low- and sufficient Pi conditions, indicating that TaPHR3-A1 positively regulated tolerance to low Pi. Introgression lines further confirmed the effect of TaPHR3-A1 in improving grain number. The Chinese wheat mini core collection and a recombinant inbred line analysis demonstrated that the favorable allele TaPHR3-A1-A associated with higher grain number was positively selected in breeding. A TaPHR3 - A1 -derived cleaved amplified polymorphic sequence marker effectively identified haplotype TaPHR3-A1-A . Our results suggested that TaPHR3-A1 was a functional regulatory factor for Pi uptake and provided useful information for marker-assisted selection for high yield in wheat. Abstract : TaPHR3-A1 is involved in Pi deficiency response in wheat, and positively regulates tolerance to low-Pi conditions. A molecular marker for TaPHR3-A1 confirmed significant associations with yield-related traits, especially grain number, in a diversity panel and mapping population.